Further evaluation of treatment duration on the resurgence of destructive behavior. Issue 1 (6th October 2022) - Greer, Brian D.; Shahan, Timothy A.; Fisher, Wayne W.; Mitteer, Daniel R.; Fuhrman, Ashley M.
Abstract : Translation of promising procedures for mitigating treatment relapse has received considerable attention recently from researchers across the basic–applied continuum. One procedure that has demonstrated mixed support involves increasing the duration of treatment as a strategy for blunting resurgence. In a recent translational study, Greer et al. (2020) failed to detect a mitigation effect of increased treatment duration on the resurgence of destructive behavior. However, design limitations may have been responsible. The present study corrected these limitations by (a) employing a sequential design to decrease the possibility of multiple‐treatment interference, (b) evaluating more treatment durations, (c) arranging treatments of fixed durations, and (d) conducting treatments of more extreme duration in a different clinical sample. Despite these improvements in experimental rigor and the testing of more extreme boundary conditions, the present study also failed to detect a mitigation effect of increased treatment duration. Likely explanations are discussed.